2014
DOI: 10.1111/een.12125
|View full text |Cite
|
Sign up to set email alerts
|

Herbivorous insect decreases plant nutrient uptake: the role of soil nutrient availability and association of below‐ground symbionts

Abstract: 1. Plants take nutrients from the rhizosphere via two pathways: (i) by absorbing soil nutrients directly via their roots and (ii) indirectly via symbiotic associations with nutrient‐providing microbes. Herbivorous insects can alter these pathways by herbivory, adding their excrement to the soil, and affecting plant–microbe associations. 2. Little is known, however, about the effects of herbivorous insects on plant nutrient uptake. Greenhouse experiments with soybean, aphids, and rhizobia were carried out to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Aphids can also alter the profiles of compounds, released from plant roots (Hoysted et al, 2018) and can also change the profiles of sugars found in AMF hyphae sharing the same host plant (Cabral et al, 2018). Moreover, aphids excrete honeydew as a result of their C rich diet of phloem sap which can be utilized as a C source by soil microbiota, thus shaping community structure and biomass (Katayama et al, 2014; Milcu et al, 2015). As more C sources become available in the root, it is possible that niches may enlarge allowing less competitive fungi to compete, reducing the dominance of abundant taxa.…”
Section: Discussionmentioning
confidence: 99%
“…Aphids can also alter the profiles of compounds, released from plant roots (Hoysted et al, 2018) and can also change the profiles of sugars found in AMF hyphae sharing the same host plant (Cabral et al, 2018). Moreover, aphids excrete honeydew as a result of their C rich diet of phloem sap which can be utilized as a C source by soil microbiota, thus shaping community structure and biomass (Katayama et al, 2014; Milcu et al, 2015). As more C sources become available in the root, it is possible that niches may enlarge allowing less competitive fungi to compete, reducing the dominance of abundant taxa.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation is that, aboveground consumers destroy leaves and interfere with photosynthesis while consuming sugars and other nutrients that are required by Rhizobium leading to poor root nodulation (Katayama et al, 2014). This is similar to conditions of inadequate light for photosynthesis that constrains symbiosis transforming Rhizobium and other mutualists into parasites (Ballhorn et al, 2016).…”
Section: Suppression Of Rhizobium By Aboveground Consumersmentioning
confidence: 99%
“…Insect herbivory can modify plant physiology (Bolton, 2009) and alter metabolite concentrations in plant tissues (Griffiths et al, 1994;Hopkins et al, 1995;Ponzio et al, 2017) as well as nutrient uptake (Katayama et al, 2014;Aziz et al, 2016). It can also modify the release of organic matter by plant roots (rhizodeposition), a major driver of soil microbial communities (Singh et al, 2004;Paterson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies showed that root herbivory can influence plant carbon sources and rhizosphere chemistry, which in turn modify the abundance of bacteria and fungi, and community physiological profiles in the rhizosphere (Grayston et al, 2001;Dawson et al, 2004;Treonis et al, 2005). Katayama et al (2014) showed that herbivory could also alter chemical element uptakes by the roots as well as nitrogen concentration of microbial origin. So far, when the effect of herbivory on plant-associated microorganisms was covered, the experiments either neglected to take into account the plant metabolites and chemical elements or did not integrate the notion of perturbation dynamics, or cultivable methods and fluorimetry were used to study microbial communities.…”
Section: Introductionmentioning
confidence: 99%